Melatonin and breast cancer: a mathematical modeling approach in blind women - Enver, Aytekin; Ayaz, Fatma (Fırat Evirgen, 2025)
Melatonin, a hormone secreted by the pineal gland, regulates circadian rhythms and exhibits strong anticancer potential through its antioxidant, immunomodulatory, and hormonal effects. This study develops a novel reaction–diffusion mathematical model to describe multiscale interactions among melatonin, breast cancer cells, and immune responses, emphasizing blind women who sustain high melatonin levels due to a lack of light perception. The model uniquely integrates hormonal, oxidative, and immune processes within a unified spatio-temporal framework, enabling joint analysis of tumor proliferation, melatonin-induced inhibition, immune cytotoxicity, and fibroblast-mediated tumor stimulation. Epidemiological evidence indicates that blind women show a markedly lower incidence of hormone-dependent cancers, attributed to continuous melatonin activity. Numerical simulations demonstrate that elevated melatonin concentrations suppress tumor growth, strengthen immune activity, and reduce fibroblast-driven promotion. Moreover, stress-related melatonin depletion is shown to disrupt tumor–immune balance, supporting the hypothesis that circadian rhythm disturbance accelerates tumor progression. The findings offer mechanistic insight into melatonin’s dual preventive and therapeutic roles and establish a quantitative link between biochemical regulation and tumor dynamics. By coupling biological data with mathematical rigor, the proposed framework advances mathematical oncology by uniting circadian biology, immunology, and tumor modeling within a single analytical structure.
Keywords: Biological Mathematics; Biyolojik Matematik